Navigating the European Union Artificial Intelligence Act for Healthcare - Busch, Felix; Kather, Jakob Nikolas; Johner, Christian; Moser, Marina; Truhn, Daniel; Adams, Lisa C.; Bressem, Keno K. (npj digital medicine, 2024)
The European Union’s recently adopted Artificial Intelligence (AI) Act is the first comprehensive legal framework specifically on AI. This is particularly important for the healthcare domain, as other existing harmonisation legislation, such as the Medical Device Regulation, do not explicitly cover medical AI applications. Given the far-reaching impact of this regulation on the medical AI sector, this commentary provides an overview of the key elements of the AI Act, with easy-to-follow references to the relevant chapters.